Analisis Kesulitan Guru Matematika SMP Negeri 1 Lendah dalam Menerapkan Pembelajaran Online pada Masa Pandemi Covid-19 - Irham.taufiq; Ugi Amri Ma'rufi; Esti Harini (UNION : Jurnal Ilmiah Pendidikan Matematika, 2022)
This research is descriptive qualitative research. The purpose of this study is to find out what difficulties are experienced by junior high school mathematics teachers in implementing online learning and solutions that can be applied to reduce these difficulties. This research was conducted at SMP Negeri 1 Lendah. The data sources are 4 mathematics teachers of SMP Negeri 1 Lendah. Data was collected by means of observation, interviews, and documentation.  The results showed that the difficulties of mathematics teachers in implementing online learning during the COVID-19 pandemic were the lack of understanding of IT, low student activity, insufficient cellphone ownership and unsupportive signals. In addition, solutions that can be done to reduce these difficulties include increasing teacher insight in the IT field, limited face-to-face learning and collaboration of all school members, teachers and students. Suggestions from this research are teachers must improve IT skills, schools must cooperate with parents, students must increase activeness in learning and researchers can use this research as a reference in research related to the effectiveness of online learning.